Pemodelan dan Visualisasi Kenaikan Muka Air Banjir di Sungai Batang Tarusan, Nagari Duku, Kecamatan XI Koto Tarusan - Zuhrifal Canrata; Dwi Marsiska Driptufany; Ilham Armi; Defwaldi Defwaldi; Fajrin Fajrin (Politeknik Kampar, 2025)
The rise in water levels of the Batang Tarusan River in Nagari Duku during the flood event from March 4 to March 7, 2024, was identified, and modeling and visualization of floodwater level increases were developed using HEC-RAS and ArcScene software. The modeling was conducted using both one-dimensional (1D) and two-dimensional (2D) approaches. The analysis results indicate that the highest recorded water level elevation reached approximately 12 meters, with an average water level of 4.45 meters. The 1D modeling demonstrated a water level rise ranging between 7 and 8 meters at each cross-section, while the 2D modeling resulted in a water depth of up to 9.65 meters, with an average Water Surface Elevation (WSE) of 12 meters. The 3D visualization, utilizing Digital Terrain Model (DTM) data, which was integrated with the Animation Manager to simulate the rise in water levels from 4.45 meters to 12.45 meters in increments of 15 cm every 30 seconds.